(3JgPjH GdJgPjHs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3JQLeI eMeO Hf YHO Gddg Hf EfSGf GdKbai GdWGFa s
(3BNQgG (B:s
(3JQLeI ejfG Hf CHj ejfG GdNQGR , ehdi YHO GdQMef Hf Yha hBNQ GdJQLeI (B: (3hCZQH GdMGce aRYe ai GdeSJOQc Cf dg UMHI hSeGAkG jJdhg ai GdPi HYOg HGH Gdfhf hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3gPg GdfSNI LRA ef GdeNWhW s
(3cJH GdcQGSGJ GdCNjQI HNW fSNI eZGjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
Keywords: (3GdJGQjNs